Meconium aspiration syndrome, fetal heart rate, and stillbirth. Literature review - Jésser M. Herrera-Salgado; Luis E. Reyes-Mendoza; Jesús C. Briones-Garduño (Revista Médica del Hospital General de México)
Meconium aspiration syndrome (MAS) is a medical condition that can affect newborn babies. It occurs when a newborn inhales meconium, which is the first stool (feces) that a baby passes in the womb. Normally, meconium is expelled after birth, but in some cases, it is released into the amniotic fluid and can be inhaled by the baby before or during delivery. This can lead to a range of respiratory problems and complications. The severity of MAS can vary, with some infants experiencing mild symptoms and others facing more severe respiratory distress. Babies with MAS may have symptoms such as rapid breathing, grunting, bluish or grayish skin color (cyanosis), and chest retractions (drawing in of the chest wall with each breath). Severe cases of MAS may require treatment in a neonatal intensive care unit. The prognosis for babies with MAS varies depending on the severity of the condition and the promptness of treatment. Most infants recover with appropriate medical care, but in severe cases, complications can occur. It is important for health-care providers to closely monitor and provide care to babies with MAS to ensure the best possible outcomes. We present a document that results from the consultation of an updated bibliography on MAS, including aspects related to its pathophysiology and complications and the considerations to be taken into account by the obstetric service.